Conditional immortalization of primary adipocyte precursor cells - Church, Christopher (Adipocyte, 2015)
The production of new adipocytes requires the differentiation of adipocyte precursor (AP) cells residing within the adipose tissue stromal-vascular compartment. The objective was to obtain an immortalized primary adipogenic cell line derived from FACS isolated committed APs using the conditional expression of SV40 T antigen. Adipocyte precursors were isolated from white adipose tissue (WAT) using FACS to remove non-adipogenic cell populations from mice expressing a conditionally regulated SV40 T antigen. APs were maintained by continuous culture and induced to undergo adipogenic differentiation. Adipogenesis, determined by Oil Red O staining, was assessed with each passage and compared to wildtype controls. Adipogenic capability was rapidly lost with increased passage number in committed APs with concurrent reduction in cell proliferation and expression of essential late adipogenic genes, including Pparγ and C/ebpα. Thus, FACS purified committed APs have limited capability to undergo expansion and subsequent adipogenic differentiation in vitro even if they are immortalized with the SV40 T antigen.